Mortality of workers employed in refractory ceramic fiber manufacturing: An update. Issue 7 (8th February 2022) - LeMasters, Grace; Lockey, James E.; Hilbert, Timothy J.; Burkle, Jeff W.; Rice, Carol H.
Abstract: This study evaluates the possible association between refractory ceramic fiber (RCF) exposure and all causes of death. Current and former employees ( n  = 1, 119) hired from 1952 to 1999 at manufacturing facilities in New York (NY) state and Indiana were included. Work histories and quarterly plant‐wide sampling from 1987 to 2015 provided cumulative fiber exposure (CFE) estimates. The full cohort was evaluated as well as individuals with lower and higher exposure, <45 and ≥45 fiber‐months/cc. The Life‐Table‐Analysis‐System was used for all standardized mortality rates (SMRs). Person‐years at risk were accumulated from start of employment until 12/31/2019 or date of death. There was no significant association with all causes, all cancers, or lung cancer in any group. In the higher exposed, there was a significant elevation in both malignancies of the "urinary organs" (SMR = 3.59, 95% confidence interval [CI] 1.44, 7.40) and "bladder or other urinary site" (SMR = 4.04, 95% CI 1.10, 10.36), which persisted in comparison to regional mortality rates from NY state and Niagara County. However, six of the nine workers with urinary cancers were known smokers. In the lower exposed, there was a significant elevation in malignancies of the lymphatic and hematopoietic system (SMR = 2.54, 95% CI 1.27, 4.55) and leukemia (SMR = 4.21, 95% CI 1.69, 8.67). There was one pathologically unconfirmed mesothelioma death. A second employee currently living with a pathologically confirmed mesothelioma was identified, but the SMR was non‐significant when both were included in the analyses. The association of these two mesothelioma cases with RCF exposure alone is unclear because of potential past exposure to asbestos. Abstract : The aim was to analyze the mortality of employees ( n  = 1, 119) hired from 1952 to 1999 at two refractory ceramic fiber (RCF) facilities. Plant‐wide sampling conducted (1987–2015) estimated cumulative fiber exposure. There were 310 deaths with no significant association with lung cancer. Two mesothelioma cases were identified. Malignancies of the urinary organs and bladder in the higher exposure group were significant (SMR = 3.59 95% CI 1.44, 7.40) and (SMR = 4.04 95% CI 1.10, 10.36).